Analysis of the Application of Character Values in the Learning Process in Grade IV Students of SDN Tiwu - Rinda Kuratul Aini (Jurnal Syntax Admiration, 2023)
Character education is an effort to balance the widespread effects of globalization. Globalization has reached every segment of society, including elementary school-aged children. There are both positive and negative impacts resulting from the prevalence of globalization. The issue at hand is the negative impact itself, and children are particularly vulnerable to these negative effects, as they are not yet capable of filtering or distinguishing between what is good and what is harmful. The aim of this research is to describe the implementation of three character values through analysis of planning, teaching execution, and learning evaluation. Additionally, the study seeks to identify the supporting and hindering factors in implementing these three character values in the fourth-grade class at SDN Tiwu Asem. This research adopts a qualitative descriptive approach, with data collected through in-depth interviews with informants. Data collection techniques also include field observations and documentation. Data validity is ensured through source triangulation, technique triangulation, and theoretical triangulation. Data analysis is carried out by collecting, reducing, presenting, and drawing conclusions from the data. The research findings indicate that the implementation of character values at SDN Tiwu Asem has been integrated into the teaching process through planning, execution, evaluation, and practical application. Supporting factors include the inclusion of character education in the curriculum and dedicated teachers who drive the implementation of character values. On the other hand, inhibiting factors include a lack of teacher understanding, student behavior, teaching execution, and the underdevelopment of a school culture to support character education.